How School Choice is Framed by Parental Preferences and Family Characteristics: A Study in Poor Areas of Lagos State, Nigeria. (February 2017) - Dixon, Pauline; Humble, Steve; Tooley, James
Abstract: This research set out to investigate how, in a low‐income area of Nigeria, parental preferences and household characteristics affect school choice for their children. A household survey was undertaken in Lagos State, Nigeria, gathering data for 556 children attending government and low‐cost private primary schools. Descriptive data show that poor parents investigate a wide range of sources to inform the decision‐making process. These include school visits, networks of relatives, friends and neighbours, and school observations. Discrete choice theory is used to model how school choice is framed by parental preferences and family characteristics. The results show a large statistically significant preference for low‐cost private schools where quality of teaching, proximity to home and strong school leadership are important to parents. The child's birth order in the family and the older the child increased the likelihood of parents choosing a government school for that child. Children living in a family unit where the father has achieved a higher level of occupation or education are more likely to attend a private school. Family income and higher maternal educational attainment are not significant characteristics in this school choice model.